Liver Transplantation Versus Liver Resection for Stage I and II Hepatocellular Carcinoma: Results of an Instrumental Variable Analysis - Li, Wei; Xiao, Haitao; Wu, Hong; Xu, Xuewen; Zhang, Yange (Frontiers in Oncology, 2021)
Background: The objective of the current study was to compare the long-term outcomes of Liver transplantation (LT) and liver resection (LR) among patients with stage I and II hepatocellular carcinoma (HCC). Methods: SEER 18 registry database for 2004 through 2015 was retrieved for the present study. A total of 1765 and 1746 patients with stage I and II (AJCC, 6th or 7th) HCC were included in the multivariable analyses and instrumental variable (IV) analyses, respectively. Propensity score matching (PSM) was performed to eliminate possible bias. Propensity score to receive LT was adjusted by a stabilized inverse probability of treatment weighting (IPTW) and standardized mortality ratio weighting (SMRW) methods. Results: In the multivariable adjusted cohort, a clear prognostic advantage of LT was observed in overall survival (OS, P < 0.001) and disease-free survival (DSS, P < 0.001) compared to patients with LR. LT rates in various Health Service Areas (HSA) was employed as our instrument. Estimates based on this instrument indicated that patients treated with LT had significantly longer OS (P = 0.001) and DSS (P < 0.001). In IV analyses stratified by clinicopathologic variables, we found that the treatment effect of LT (OS) was consistent across all the subgroups. Regarding DSS in IV analyses, the subgroup analyses observed that LT had better DSS across all subgroups except for similar results in the older patients (interaction P value = 0.039) and the non-White population (interaction P value = 0.041). In the propensity-matched cohort, patients with LT still had better OS (P < 0.001) and DSS (P < 0.001) compared to patients with LR. In both IPTW and SMRW cohorts, patients who underwent LT had better OS (both P values < 0.001) and DSS (both P values < 0.001). Conclusions: LT provided a survival benefit for marginal patients with stage I and II HCC. These results suggest that if LT rates were to increase in the future, average survival may also be expected to increase. However, for some special populations such as the elderly patients, owing to the similar outcomes between LT and LR, the selection of LT should be cautious.